Reinfection with SARS-CoV-2: An inconvenient truth? - Pedro Sonie; Jorge Manuel-Silva; Alexandra Rafael; Luis Amorim-Alves (Journal of Family Medicine and Primary Care, 2022)
Data show that antibody-related immunity against SARS-CoV-2 may not be long-lasting. We report two cases regarded as cured from COVID-19, which presented again with symptoms and a positive SARS-CoV-2 RT-PCR test. Case one, a 60-year-old male, had a biphasic presentation of symptoms compatible with COVID-19 infection, associated with a positive RT-PCR test. Case two, a 25-year-old female, had a first positive RT-PCR test during hospital screening, and months later a symptomatic presentation of COVID-19, associated with a positive RT-PCR test. All cases were immunocompetent. Anti-IgG-SARS-CoV-2 blood samples were negative in both. Elevation of analytical inflammatory markers suggested new infection in both cases. COVID-19 reinfection may be a differential diagnosis and primary care physicians should acknowledge it. Previously cured patients should be encouraged to comply with health public preventive measures.